1994
DOI: 10.1159/000261636
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Dental Plaque Deposition in Humans by Oolong Tea Extract

Abstract: The inhibitory effect of oolong tea extract (OTE) containing polymerized polyphenols on plaque deposition was examined in 35 human volunteers. Thirty-five human volunteers, aged 18-29 years, who received extensive oral prophylactic procedures were requested to refrain from all oral hygiene procedures for 4 days, and to rinse their mouth with 0.5 mg/ml OTE solution in 0.2% ethanol before and after every intake of food and before sleeping at night. No restriction regarding meals was given during the test period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 5 publications
1
47
0
2
Order By: Relevance
“…Animal studies have demonstrated that various tea extracts prevented or reduced caries formation (46,48,49,55). Clinical trials have also shown that drinking tea (without added sugar) is associated with lower caries levels in humans (30,47,50). Our previous study in adult humans found that rinsing with black tea extract resulted in a significantly less-pronounced plaque pH fall and a lower plaque index than the water-rinse group (70).…”
mentioning
confidence: 99%
“…Animal studies have demonstrated that various tea extracts prevented or reduced caries formation (46,48,49,55). Clinical trials have also shown that drinking tea (without added sugar) is associated with lower caries levels in humans (30,47,50). Our previous study in adult humans found that rinsing with black tea extract resulted in a significantly less-pronounced plaque pH fall and a lower plaque index than the water-rinse group (70).…”
mentioning
confidence: 99%
“…Compounds present in both green and oolong teas have been studied on dental caries in a simple form and individually (6,7). Animals and humans given tea compounds in their drinking water develop fewer dental caries and less plaque formation than those drinking plain water (8)(9)(10)(11). Drinking green tea may also help prevent sore throats and colds, since it helps fight the bacteria harboring in the throat (12), another reason that encouraged us to work on Iranian green tea other than its healing effect on burn and wound, which was also in the area of our studies (13,14), was a traditional belief for its masking the bad breath.…”
Section: Moghbel a Et Al Evaluation The Effect Of Green Tea Extract mentioning
confidence: 99%
“…S. mutans 로부터의 glucosyltransferase(Gtase)에 의해 합성되는 불용성 glucan 또한 치석을 형 성하여 산을 축적시킴으로서 치아 에나멜층의 국소적 탈미네랄 화를 야기 시킨다 (9 2) Glucosyltransferase(GTase)의 활성저해 S. mutans 균이 생성하는 GTase가 sucrose를 이용하여 점착성 을 지니며 불용성인 glucan을 합성, dental plaque를 형성하므로, 앞선 실험결과 S. mutans 균에 대해 항균활성이 높은 것으로 나 타난 표고버섯, 영지버섯 및 만가닥버섯만을 대상으로 이들 추출 물의 GTase 활성 저해 효과를 조사해 보았다 (Fig. 1) …”
Section: 서 론unclassified